Alginate-based Composite Microspheres: Preparations and Applications for Bone Tissue Engineering - Jayachandran, Venkatesan; Murugan, Sesha S.; Dalavi, Pandurang Appana; Gurushanthappa Vishalakshi, Yashaswini Devi; Seong, Gi Hun (Current Pharmaceutical Design, 2022)
Alginate-based biomaterials have been extensively studied for bone tissue engineering. Scaffolds, microspheres, and hydrogels can be developed using alginate, which is biocompatible, biodegradable, and able to deliver growth factors and drugs. Alginate microspheres can be produced using crosslinking, microfluidic, three-dimensional printing, extrusion, and emulsion methods. The sizes of the alginate microspheres range from 10 μm to 4 mm. This review describes the chemical characterization and mechanical assessment of alginatebased microspheres. Combinations of alginate with hydroxyapatite, chitosan, collagen, polylactic acid, polycaprolactone, and bioglass were discussed for bone tissue repair and regeneration. In addition, alginate combinations with bone morphogenetic proteins, vascular endothelial growth factor, transforming growth factor beta- 3, other growth factors, cells, proteins, drugs, and osteoinductive drugs were analyzed for tissue engineering applications. Furthermore, the biocompatibility of developed alginate microspheres was discussed for different cell lines. Finally, alginate microsphere-based composites with stem cell interaction for bone tissue regeneration were presented. In the present review, we have assessed the preclinical research on in vivo models of alginatebased microspheres for bone tissue repair and regeneration. Overall, alginate-based microspheres are potential candidates for graft substitutes and the treatment of various bone-related diseases.
Keywords: microspheres